"Arthrocaulon meridionalis" (Chenopodiaceae), a new species of Mediterranean flora - Ramírez, Esteban; Rufo, Lourdes; Sánchez-Mata, Daniel; de la Fuente, Vicenta (Mediterranean Botany, 2018)
A new species of Arthrocaulon Piirainen & G. Kadereit, A. meridionalis is described. This diploid taxon is known from the islands of Sicily and Sardinia and from circum-Mediterranean territories (from North Africa to the Anatolian Peninsula in Turkey and as far as the Persian Gulf on the Asian continent). The distinctive macro-, micromorphological and chorological features of this taxon are given.